If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = -9x Solving 63 = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 63 + 9x = -9x + 9x Combine like terms: -9x + 9x = 0 63 + 9x = 0 Add '-63' to each side of the equation. 63 + -63 + 9x = 0 + -63 Combine like terms: 63 + -63 = 0 0 + 9x = 0 + -63 9x = 0 + -63 Combine like terms: 0 + -63 = -63 9x = -63 Divide each side by '9'. x = -7 Simplifying x = -7
| x^2-21x-108=0 | | 14-.20(j-10)=.4(25+j) | | 3=3+5x+6x | | (3x+5)+2x=180 | | 2a-5=3a-15 | | 9b^2+15b-14=0 | | 42-r-2(13-5r)+7=85 | | 3x^2+90x=180 | | w+6=334 | | (x-5)-4(x-6)=9 | | 16x^4-5x^2-11=0 | | -3.2x=8.48 | | (1/8)(5y+64)=.25(20+2y) | | 3x=-2.25 | | 334=w(w+6) | | [36]/3= | | -1-15=-3t+t | | 2g=g+5 | | [36]3= | | 6+2(3j-2)=4(1-j) | | 5x-10+3x=7+8x-17 | | x+x+2+x+4+x+6=188 | | -16t^2+484= | | 4x-x+6=3x-2+6 | | w^3-5w^2-14w=0 | | 6(4-2x)=3(4x+8) | | 12+2x=4x/4+2x | | 0=12.5x-4.9x^2 | | -(8y+3)-(-7y-7)=-2 | | -3p-4=2p | | a+3-4=-1 | | -5+13x=-6x^2 |